E-198 Facial pain caused by a cavernous sinus aneurysm treated with endovascular flow diversion: case report and review of the literature. (4th August 2020) - Larson, A; Mehta, T; Grande, A
Abstract : Flow diversion is a commonly-used endovascular modality to treat intracavernous aneurysms. Cases of intracavernous aneurysms causing facial pain are rare, and flow diversion may represent a viable treatment option in order to alleviate pain caused by these aneurysms. We present the case of a 53-year-old woman who presented with a two-year history of persistent, left-sided and facial pain and numbness located in the left V1-V2 distribution of the Trigeminal nerve. A brain MRI was obtained which showed a left internal carotid artery aneurysm projecting infero-laterally within the cavernous sinus and possibly compressing left V1 and V2 roots of the Trigeminal nerve. This was further investigated and confirmed with digital subtraction angiography. To reduce mass effect, the aneurysm was treated with flow-diversion rather than coil-embolization. Her pain and numbness gradually improved with near-complete resolution at 6 months post-treatment. 6-month follow-up angiography demonstrated minimal residual filling of the aneurysm suggesting a reduction in size of the aneurysm sac. This case, in addition to prior reports which we review here, demonstrate the ability of flow diversion to treat facial pain secondary to intracavernous aneurysms. Disclosures: A. Larson: None. T. Mehta: None. A. Grande: None.